NOMA -Spatial Modulation: Solving Power Allocation Issue via Improved Black Widow Optimization. (January 2023) - Jadhav, Kishor; Vidyarthi, Abhay
Highlights: This work models a new NOMA based SM system that considers power allocation issue as the optimization problem to minimize the maximum symbol error rate (SER) or minimize the average SER. Here, NOMA-APM with scrambling is considered as the new perception, which ensures increased throughput. To solve this optimization issue, an enhanced or improved optimization strategy is introduced. Here, Black Widow Optimization with New Mating Behavior (BWO-NMB) is deployed for attaining minimal error and power utilization. Eventually, the enhancement of BWO-NMB based technique is confirmed over other schemes as well as for with and without AS. Abstract: Developing next-generation multiple access (MA) schemes that can provide high spectral efficiency (SE) and a higher connection scale is crucial for managing the unpredictable traffic expansion of next-generation wireless interactions. Non-orthogonal multiple access (NOMA) in the power domain has recently been the subject of in-depth research. To minimize either the average or maximum symbol error rate (SER), this work develops a novel NOMA-based SM system that considers power allocation. The new perception, which guarantees higher throughput, is NOMA-APM with scrambling in this context. A more advanced or better optimization approach addresses this optimization problem. Here, Black Widow Optimization with New Mating Behavior (BWO-NMB) is deployed for attaining minimal error and power utilization. Eventually, the enhancement of BWO-NMB based technique is confirmed over other schemes as well as for with and without AS.